Perspectives on Employment Integration, Mental Illness and Disability, and Workplace Health - Nene Ernest Khalema; Janki Shankar (Advances in Public Health)
This paper reviews the literature on the interplay between employment integration and retention of individuals diagnosed with mental health and related disability (MHRD). Specifically, the paper addresses the importance of an integrative approach, utilizing a social epidemiological approach to assess various factors that are related to the employment integration of individuals diagnosed with severe mental illness. Our approach to the review incorporates a research methodology that is multilayered, mixed, and contextual. The review examines the literature that aims to unpack employers’ understanding of mental illness and their attitudes, beliefs, and practices about employing workers with mental illness. Additionally we offer a conceptual framework entrenched within the social determinants of the mental health (SDOMH) literature as a way to contextualize the review conclusions. This approach contributes to a holistic understanding of workplace mental health conceptually and methodologically particularly as practitioners and policy makers alike are grappling with better ways to integrate employees who are diagnosed with mental health and disabilities into to the workplace.